Adolescence as a critical window for developing an alcohol use disorder: Current findings in neuroscience - Nixon, Kimberly (2010)
PURPOSE OF REVIEW: Alcohol consumption during adolescence greatly increases the likelihood that an alcohol use disorder will develop later in life. Elucidating how alcohol impacts the adolescent brain is paramount to understanding how alcohol use disorders arise. This review focuses on recent work addressing alcohol's unique effect on the adolescent brain. RECENT FINDINGS: The unique and dynamic state of the developing adolescent brain is discussed with an emphasis on the developmentally distinct effect of alcohol on the dopaminergic reward system and corticolimbic structure and function. Reward neurocircuitry undergoes significant developmental shifts during adolescence, making it particularly sensitive to alcohol in ways that could promote excessive consumption. In addition, developing corticolimbic systems, including the prefrontal cortex and hippocampus, exhibit enhanced vulnerability to alcohol-induced damage. Disruption of white matter integrity, neurotoxicity and inhibition of adult neurogenesis may underlie alcohol-mediated cognitive dysfunction and lead to decreased behavioral control over consumption. SUMMARY: In adolescents, alcohol interacts extensively with reward neurocircuitry and corticolimbic structure and function in ways that promote maladaptive behaviors that lead to addiction. Future work is needed to further understand the mechanisms involved in these interactions. Therapeutic strategies that restore proper reward neurochemistry or reverse alcohol-induced neurodegeneration could prove useful in preventing emergence of alcohol use disorders.